TEKNIK PEMBESARAN UDANG VANAME (Litopenaeus vannamei) DI PT. KEBAYORAN PRIMA BAHARI DESA EMPAN KECAMATAN LABUHAN BADAS - Yuna Julia Putri (Program Studi Ilmu Perikanan, Fakultas Ilmu dan Teknologi Hayati, Universitas Teknologi Sumbawa, 2025)
This study aims to identify the technique of vannamei shrimp (Litopenaeus vannamei) grow-out at PT. Kebayoran Prima Bahari, Sumbawa. This activity was conducted through a two-month internship. The method used was participatory observation and documentation. The results showed that the grow-out process includes pond preparation, seed stocking, maintenance, water quality management, feeding, and harvesting. Feeding was carried out using blind feeding and automatic feeders by calculating the Feed Conversion Ratio (FCR) and Survival Rate (SR). The grow-out result showed a survival rate of 85% and an FCR of 1.4. Thus, the applied technique is proven effective and efficient.